Livestock Breeding for Climate-Resilient Agriculture: Genetic Improvements and Sustainable Practices for Rural Development - Diana Magfiroh Magfiroh (Livestock Science & Innovation Journal, 2025)
Backround: Climate change significantly threatens livestock production, especially in tropical and subtropical regions where heat stress hampers productivity and food security. Genetic improvement via selective breeding provides a sustainable approach to developing climate-resilient livestock. Objective: This study assessed the effectiveness of selective breeding in creating heat-tolerant cattle populations, comparing outcomes across indigenous breeds and exploring physiological, productive, and molecular mechanisms.Method: A 36-month controlled breeding experiment was conducted using 480 cattle from three breeds: Qinchuan (n=160), Dengchuan (n=160), and Danish Large White crosses (n=160). Findings and Implications: The cattle were exposed to controlled heat stress (32-38°C, 70-85% RH), with phenotypic traits (growth rate, feed efficiency, heat tolerance index), physiological parameters (rectal temperature, respiration rate, hormonal profiles), and molecular markers (TPM3, TMEM95, SNP loci) assessed. Breeding values were estimated using BLUP, with a 10% selection intensity for heat tolerance. Heat-tolerant lines showed an 18.3% higher heat tolerance index (P<0.01), 12.7% improved feed efficiency, and 8.4% faster growth under heat stress. Physiological data revealed lower rectal temperatures (38.6±0.3°C vs. 39.4±0.5°C, P<0.01) and reduced respiration rates in selected cattle. Conlusion: Molecular analysis identified 23 significant SNPs associated with heat tolerance. Selective breeding effectively enhances climate resilience, improving heat tolerance and productivity while offering favorable economic benefits. Molecular markers accelerate genetic gains for sustainable livestock production under climate change.